Coping strategies and perception toward drugs, electronic gadgets, and media in relation to stress: A cross-sectional study among residents of a suburban area - Manisha Arora; Archana Singh; Ajit Kumar Singh; Vishal Sharma; Atul Kotwal (Wolters Kluwer Medknow Publications, 2021)
Background and Objectives: Stress is an indispensable part of modern-day living. The study deals with coping strategies by the participants and their perception toward drugs, electronic gadgets, and media as stress creators, busters, or relievers. Materials and Methods: A cross-sectional study was conducted among 400 community dwellers in a suburban area of Delhi. A structured questionnaire with Likert scale was used to assess coping strategies to stress and perception of use of electronic gadgets, media, and substance abuse as stress creators, busters, and relievers. Results: For coping strategies, 52.8% (95% confidence interval: 47.73-57.73) of the participants wanted to discuss problems with their families, but others considered mobile phones (51.5%, 46.48, 56.50), television (70.5%, 65.77, 74.93), and social networking sites (33.5%, 28.89, 38.36) to be their stress busters than creators. An age-associated statistically significant difference in perception about stress creator and buster scores between younger versus older was observed (P = 0.000), whereas gender-wise males perceived substance abuse to be a stress reliever in contrast to females (P = 0.000). Conclusion: Family plays an important role in the mitigation of stress. However, excess reliance on social media by younger people and substance abuse by males in stressful situations need to be addressed adequately.